A combined wind and wave energy-converter concept in survival mode: Numerical and experimental study in regular waves with a focus on water entry and exit. (February 2017) - Wan, Ling; Greco, Marilena; Lugni, Claudio; Gao, Zhen; Moan, Torgeir
Abstract: A combined wind and wave energy converter concept, named STC concept was proposed. Model tests were performed in terms of operational and survival modes. Water entry and exit phenomena as well as green water on deck were observed during the survivability model tests. In this paper, a nonlinear numerical model based on a blended station-keeping potential-flow solver with a local impact solution for bottom slamming events and an approximated model for the water shipped on the deck is proposed to simulate these nonlinear phenomena. Physical investigation of the water entry and exit process was firstly carried out and uncertainty analysis of the model test results were performed. Numerical comparisons between the nonlinear solver and model test results are then performed in terms of mean, wave frequency and double wave frequency motion response components. The slamming and green water involved in the water entry process are specially investigated, in terms of the physical evolution and the effects on the dynamic motion responses. The validation work on the occurrence of slamming and water on deck as well as the slamming pressure are performed.